Technology Integration for Quality Education: A study for Equity and Justice - Thapa, Amrit B. (Bodhi: An Interdisciplinary Journal, 2022)
There is a long history of more than six decades of technological development and its incorporation in education. A large volume of literature and research focuses on the importance of technology integration in order to create an educational environment conducive to a higher-order learning opportunity. Adaptation of technology became more pertinent in the present context of COVID-19 pandemic. However, there are concerns about whether all learners worldwide are getting equitable access to technology in learning. In this context, this paper studies some policy documents from Nepal to explore how technology is integrated to enhance learning. Further, this paper compares Nepal's technological integration based on the common core state standards from the United States. This literature review identifies that Nepal's educational authorities need serious attention to invest in technological infrastructure and prepare for technology integration in education. This paper aims to inform and evoke policymakers, school/college leaders, teachers, and parents to put an effort to incorporate technology as one of the inevitable means to quality education.